Ginger Extract Increases GLUT-4 Expression Preferentially Through AMPK Than PI3K Signalling Pathways in C2C12 Muscle Cells - Tajik Kord, Marjan (Diabetes Metab Syndr Obes, 2020)
PURPOSE: There are two signal transduction pathways related to glucose metabolism in C2C12 mouse myoblast cells; one through AMP-activated protein kinase (AMPK), and the other through phosphoinositide 3-kinase (PI3K). Ginger is reported to have hypoglycemic effects. The aim of this study was to determine the exact mechanism of action of ginger in those pathways. METHODS: C2C12 cells were seeded to four separate experimental groups; Control: treated with 50 μg/mL DMSO in the absence of any inhibitor; Treatment 1: treated with 50 μg/mL ethyl acetate ginger extract without any inhibitor; Treatment 2: treated with 50 μg/mL extract in the presence of 20 μM AMPK inhibitor; Treatment 3: treated with 50 μg/mL extract in the presence of 25 μM PI3K inhibitor. The amount of GLUT-4 protein (an important glucose transporter) was determined in cytosolic and membrane fractions using sodium dodecyl sulfate polyacrylamide gel electrophoresis and Western blotting. RESULTS: GLUT-4 concentration was significantly higher in the membrane fraction of cells treated with ethyl acetate ginger extract in the absence of any inhibitor in comparison with cells treated with this extract in the presence of each of the inhibitors (P-value < 0.05). GLUT-4 quantity in the membrane fractions in all groups was more than cytosolic fractions. The amount of GLUT-4 in membrane fraction of treated cells in the presence of PI3K inhibitor was higher than in the cells treated with this extract in the presence of AMPK inhibitor (P-value < 0.05). CONCLUSION: Ethyl acetate ginger extract affects the amount of GLUT-4 protein in membrane and cytosolic fractions of C2C12 myoblast cells mostly through AMPK pathway but less via PI3K.